An artificial leather and its two-step production process

CN122879990APending Publication Date: 2026-10-09KEYI FUJIAN MICROFIBER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611287521.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而,现有超纤内里革在仿真皮质感方面仍存在明显不足:一方面,现有超纤革的表面纹理多通过压纹辊热压或离型纸转移形成,纹理排列具有明显的周期性和规律性,与天然真皮粒面的无序自然形态存在较大差距,视觉上容易识别为人造材料;另一方面,现有超纤革的表面涂层多为致密聚氨酯层,缺乏真皮表层的微多孔结构,触感偏滑腻而非真皮的温润爽滑感,且涂层的透湿通道被堵塞,进一步降低了材料的透气性能

Benefits of technology

[0026]1.本发明通过在聚氨酯面层薄膜外表面设置无序仿天然头层皮粒面纹理,将类毛孔凹陷的等效直径、深度和分布密度控制在特定范围内,并确保纹理无周期性重复单元,使合成革的表面肌理在视觉和触觉上接近天然头层皮的自然形态,克服了现有超纤革纹理规则刻板、仿真度低的缺陷。面层采用离型纸转移预制薄膜的方式成型,纹理形态由离型纸表面的无序雕刻肌理决定,避免了压纹辊工艺带来的周期性重复花纹。同时面层内部设置2~8μm的连通微孔并复配有机硅微粉,赋予面层接近真皮的温润爽滑触感和良好的透湿性能,使成品在仿真皮质感方面较普通超纤内里革有明显提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a kind of simulation leather lining microfiber synthetic leather and its veneer two-knife production process, belong to synthetic leather technical field.The synthetic leather is in order from front to back simulation leather grain micro-porous polyurethane surface layer, water-based polyurethane bonding transition layer, island type three-dimensional network microfiber non-woven fabric substrate and superfine flocking back surface layer, wherein surface layer is polyurethane surface layer film with simulation leather texture, outer surface is provided with unordered natural head layer skin grain texture.Its production process adopts veneer two-knife method of first veneer composite and then twice cutting and repairing, one knife rough repair is cut to about 0.70mm to semi-finished product thickness, two-knife fine repair is controlled to about 0.65mm to total thickness of finished product.The synthetic leather of the application has genuine leather texture and the wear resistance and folding air permeability of microfiber material, and the thickness uniformity is good, suitable for the lining material of shoes and bags.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of synthetic leather technology, and in particular to a simulated leather lining microfiber synthetic leather and its two-cut bonding process. Background Technology

[0002] The lining materials of footwear and bags come into direct contact with the user's skin, and their feel, breathability, abrasion resistance, and folding resistance directly affect the product's wearing comfort and lifespan. Currently, lining materials on the market are mainly divided into two categories: natural leather and synthetic leather. Natural leather, with its naturally fine grain texture, good breathability, and comfortable feel, has long been considered the preferred choice for high-end lining materials. However, natural leather has inherent drawbacks such as high cost, large batch variations, poor water resistance, and susceptibility to mildew. Furthermore, limitations in raw material supply make large-scale standardized production difficult, failing to meet the demand of the mid-to-low-end footwear and bag market for high-quality, cost-effective lining materials.

[0003] Ordinary polyurethane (PU) synthetic leather, a type of synthetic leather, holds a major market share in lining materials due to its low cost, rich colors and patterns, and ease of mass production. However, ordinary PU synthetic leather generally uses non-woven or woven fabric as the base, with a polyurethane coating on the surface to form a leather-like texture. Its simulation is low, and it feels hard and plastic, lacking the natural texture and skin-friendly feel of genuine leather. At the same time, ordinary PU synthetic leather has poor breathability and moisture permeability, which can easily cause a stuffy feeling after long-term wear. In addition, the bonding strength between the coating and the base is insufficient, and problems such as coating peeling and surface fuzzing are prone to occur after repeated bending and friction. Its abrasion resistance and folding resistance are insufficient to meet the high-frequency use requirements of footwear linings.

[0004] Microfiber synthetic leather (hereinafter referred to as microfiber leather) is a new generation of artificial leather material developed in recent years. It is made by impregnating and surface treating microfiber nonwoven fabric with island-type microfiber as the base. It is superior to ordinary PU synthetic leather in terms of mechanical properties such as abrasion resistance, folding resistance, and tear strength. It also has a three-dimensional network pore structure, which improves breathability. However, existing microfiber lining leather still has obvious shortcomings in simulating the feel of leather: on the one hand, the surface texture of existing microfiber leather is mostly formed by hot pressing with embossing rollers or transfer with release paper. The texture arrangement has obvious periodicity and regularity, which is quite different from the disordered natural form of the grain surface of natural leather. It is visually easy to identify as an artificial material. On the other hand, the surface coating of existing microfiber leather is mostly a dense polyurethane layer, which lacks the microporous structure of the surface of genuine leather. The touch is more slippery than the warm and smooth feel of genuine leather. Moreover, the moisture permeability channels of the coating are blocked, which further reduces the breathability of the material.

[0005] In terms of production technology, the current conventional production process for microfiber synthetic leather is as follows: first, the microfiber base material is slit and its thickness is determined, and then a polyurethane surface layer is coated or laminated onto the base material surface. This process of slitting the base material first and then laminating the surface has an inherent drawback: the thickness fluctuation of the adhesive layer and the unevenness of the lamination pressure during the lamination process can lead to deviations in the overall thickness of the finished product. Furthermore, micro-bubbles or protrusions are prone to form at the interface between the lamination layer and the base material after lamination. There is a lack of effective correction methods to eliminate these defects, resulting in a large thickness tolerance of the finished product, usually above ±0.03mm. For footwear lining materials that require uniform thickness, uneven thickness leads to a decrease in cutting utilization and an increase in sewing difficulty. In addition, in the current process, the semi-finished product after lamination usually goes directly into the post-processing stage, and the thickness deviation of the surface texture layer and the back of the base material cannot be accurately corrected. There is room for improvement in both yield and surface quality.

[0006] Therefore, how to develop an inner synthetic leather that combines the natural texture and skin-friendly feel of genuine leather with the excellent mechanical properties and breathability of microfiber materials, while improving the uniformity of finished product thickness and production yield through process improvement, has become an urgent technical problem to be solved in the field of microfiber synthetic leather. Summary of the Invention

[0007] The purpose of this invention is to overcome the shortcomings of existing technologies and to propose a simulated leather lining microfiber synthetic leather and its two-cut manufacturing process for the veneer.

[0008] To achieve the above objectives, the present invention adopts the following technical solution: a simulated leather lining microfiber synthetic leather, which, from the front to the back, comprises a simulated leather texture microporous polyurethane surface layer, a water-based polyurethane bonding transition layer, an island-type three-dimensional mesh microfiber nonwoven fabric base material, and an ultra-fine brushed back layer.

[0009] Preferably, the simulated leather texture microporous polyurethane surface layer is a polyurethane surface layer film with simulated leather texture. Its outer surface has a disordered imitation natural top-grain leather grain texture. The texture is composed of irregularly distributed pore-like depressions and smooth grain-like protrusions. The equivalent diameter of the pore-like depressions is 35-65 μm, the depression depth is 7-16 μm, and the distribution density per unit area is 110-170 per cm². 2 The overall surface undulation difference does not exceed 18μm, and there are no periodic repeating units.

[0010] Preferably, the original thickness of the island-type three-dimensional mesh microfiber nonwoven fabric substrate is 0.6 mm. After fiber opening and weight reduction treatment, it forms a three-dimensional through-pore structure with a fiber filament fineness of 0.05 to 0.12 D and a porosity of 68% to 75%.

[0011] Preferably, the thickness of the simulated leather texture microporous polyurethane surface layer is 0.04 to 0.06 mm, and the interior is uniformly distributed with interconnected micropores with a pore size of 2 to 8 μm. The surface layer contains 0.5 to 1.2 wt% organosilicon micro powder.

[0012] Preferably, the thickness of the waterborne polyurethane adhesive transition layer is 0.02 to 0.03 mm, and it is formed by curing with waterborne polyurethane adhesive.

[0013] Preferably, the abrasion length of the ultrafine abrasion back layer is 0.01 to 0.02 mm, and the surface fibers are fine and flat.

[0014] Furthermore, the present invention also provides a two-cut manufacturing process for laminated microfiber synthetic leather with simulated leather lining, comprising the following steps:

[0015] (1) Substrate pretreatment: Take a 0.6mm thick island-type microfiber nonwoven fabric, and after alkali reduction fiber opening, water washing, and 120℃ pre-forming, perform light abrasion treatment on the back side to obtain island-type three-dimensional mesh microfiber nonwoven fabric substrate for use.

[0016] (2) Textured surface layer prefabrication: Select matte release paper with disordered imitation natural first-grain leather grain texture, coat the surface of the release paper with microporous polyurethane slurry containing 0.5 to 1.2 wt% organosilicon micro powder, and dry in sections to form a polyurethane surface layer film with simulated leather texture for later use.

[0017] (3) Rough trimming: Water-based polyurethane adhesive is uniformly coated on the front side of the island-type three-dimensional mesh microfiber nonwoven fabric substrate. The polyurethane surface film with simulated leather texture is bonded by hot press roller. After curing, the first trimming and thickness determination are carried out to cut the overall thickness to 0.70±0.02mm to obtain the semi-finished product after rough trimming.

[0018] (4) Second-cut finishing: The semi-finished product after rough finishing is precision-cut a second time. The texture layer on the front is finely finished to ensure that the texture depression depth is consistent. The thickness of the base material on the back is finely finished. Finally, the total thickness of the finished product is controlled at 0.65±0.01mm. After finishing, the back is subjected to a second ultra-fine grinding process.

[0019] (5) Post-processing: After washing, softening, drying at 110℃ and rolling, a simulated leather lining microfiber synthetic leather is obtained.

[0020] Preferably, in step (1), the alkali reduction fiber opening uses a sodium hydroxide solution with a mass fraction of 8% to 12%, the treatment temperature is 95 to 100°C, and the treatment time is 40 to 60 minutes.

[0021] Preferably, the drying temperatures in step (2) are 80℃, 110℃ and 130℃ respectively, and the drying time for each segment is 2 to 4 minutes.

[0022] Preferably, in step (3), the temperature of hot pressing is 90-100℃, the pressure is 0.3-0.5MPa, and the bonding is left to stand for 12 hours after bonding.

[0023] Preferably, in step (3), the first sectioning is performed using a strip cutting tool with a feed rate of 0.08 to 0.12 mm / pass.

[0024] Preferably, in step (4), the second finishing process uses a precision grinding wheel slicing machine with a feed rate of 0.02 to 0.04 mm / pass.

[0025] Compared with the prior art, the beneficial effects of the present invention are:

[0026] 1. This invention creates a disordered, natural-grain leather-like texture on the outer surface of a polyurethane surface film. The equivalent diameter, depth, and distribution density of the pore-like depressions are controlled within a specific range, ensuring that the texture has no periodic repeating units. This makes the surface texture of the synthetic leather visually and tactilely close to the natural form of natural top-grain leather, overcoming the shortcomings of existing microfiber leathers with regular, rigid textures and low simulation. The surface layer is formed using a release paper transfer pre-made film method, with the texture determined by the disordered engraving texture on the release paper surface, avoiding the periodic repeating patterns caused by the embossing roller process. Simultaneously, the surface layer contains interconnected micropores of 2–8 μm and is compounded with organosilicon micropowder, giving it a warm, smooth feel close to genuine leather and good moisture permeability, significantly improving the simulated leather feel of the finished product compared to ordinary microfiber lining leather.

[0027] 2. This invention adds a water-based polyurethane bonding transition layer between the surface film and the substrate. This transition layer is formed by curing with a water-based adhesive, leaving no solvent residue. It enhances the interfacial bonding strength between the surface film and the microfiber substrate, preventing the surface film from peeling off after repeated bending. It also buffers the hardness difference between the surface film and the substrate, resulting in a soft, non-stiff finished product. The introduction of the water-based transition layer also avoids the swelling and damage to the pore structure of the microfiber substrate caused by solvent-based adhesives, preserving the three-dimensional interconnected pores of the substrate and helping to maintain the breathability and moisture permeability of the finished product.

[0028] 3. This invention employs a two-step lamination process, involving first laminating the surface and then performing two separate trimmings to determine the thickness. This differs from the conventional process of first trimming the substrate and then laminating. The first rough trimming, performed after lamination, uses a belt-type slitting blade to cut the semi-finished product to approximately 0.70mm, effectively removing thickness fluctuations and interface bubbles in the lamination layer, resulting in a preliminary uniform thickness. The second fine trimming uses a precision grinding wheel slitting machine with a smaller feed rate to precisely correct the thickness of the front texture layer and the back substrate, controlling the total thickness of the finished product to 0.65±0.01mm. This division of labor between the two trimming steps ensures both trimming efficiency and precise thickness control, significantly reducing thickness tolerance compared to traditional processes and effectively improving cutting utilization and production yield.

[0029] 4. This invention uses a 0.6mm original thickness island-type microfiber nonwoven fabric as the base material. After alkali reduction and fiber opening, it forms a three-dimensional interconnected pore structure with a fiber filament fineness of 0.05-0.12D and a porosity of 68%-75%, providing the finished product with excellent breathability, moisture permeability, abrasion resistance, and folding resistance. The back of the base material is treated with ultra-fine brushing to form a dense, flattened fiber layer of 0.01-0.02mm, which not only improves the adhesion to shoe uppers or bag substrates but also prevents back fiber shedding and contamination of the contact surface, making it suitable for use as linings in footwear and bags. Detailed Implementation

[0030] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with existing known technologies. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.

[0031] In the following embodiments, the water-soluble pore-forming agent used in the microporous polyurethane slurry is polyethylene glycol 400 (PEG-400), which is dispersed in the polyurethane resin phase in the form of tiny droplets during the drying process and is dissolved in water during the post-treatment water washing step, thereby forming interconnected micropores inside the surface layer.

[0032] Example 1: A specific two-cut manufacturing process for imitation leather lining microfiber synthetic leather, including the following steps:

[0033] (1) Substrate pretreatment: Take a 0.6 mm thick island-type microfiber nonwoven fabric (the marine phase is polyethylene, the island phase is polyester, and the composite ratio is 45:55), treat it with 8% sodium hydroxide solution at 95℃ for 40 min to perform alkali reduction fiber opening, remove the marine phase components, wash it with hot water until neutral, pre-shape it at 120℃ for 3 min, and then use a 240 mesh sander to lightly abrade the back of the substrate with an abrasion pressure of 0.2 MPa to obtain an island-type three-dimensional mesh microfiber nonwoven fabric substrate with a fiber filament fineness of 0.05D and a porosity of 68%, for later use;

[0034] (2) Pre-fabrication of textured surface layer: Matte release paper (60° gloss 3.2) with disordered imitation natural first-grain leather grain texture engraved on the surface is selected. Microporous polyurethane slurry (polyurethane solid content 30%, DMF / toluene = 7:3, 0.5wt% organosilicon micro powder and 3.2wt% polyethylene glycol 400 as water-soluble pore-forming agent) is coated on the surface of the release paper with a 120-mesh squeegee. It is then dried at 80°C for 2 min, 110°C for 2 min and 130°C for 2 min in sequence to form a polyurethane surface layer film with a thickness of 0.04 mm, an internal pore diameter of 2-4 μm and interconnected micropores with simulated leather texture. The equivalent diameter of the pore-like depressions on the outer surface texture is 35 μm, the depression depth is 7 μm and the distribution density is 110 / cm. 2 The overall surface undulation difference is 15μm, ready for use;

[0035] (3) Rough finishing: Water-based polyurethane adhesive (25% solid content) is uniformly coated on the front side of the island-type three-dimensional mesh microfiber nonwoven fabric substrate using an 80-mesh roller coating method, with an adhesive application rate of 36g / m. 2 A polyurethane surface film with simulated leather texture is bonded to the surface using a hot press roller at a temperature of 90℃, a pressure of 0.3MPa, and a bonding speed of 6m / min. After bonding, the film is left to stand and mature at 25℃ for 12 hours. After maturation, a belt-type slitting knife is used for the first trimming and thickness determination, with a cutting depth of 0.08mm / pass, reducing the overall thickness to 0.70±0.02mm to obtain a rough-trimmed semi-finished product.

[0036] (4) Second-cut finishing: The semi-finished product after rough finishing is cut a second time using a precision grinding wheel slicing machine with a feed rate of 0.02mm / pass. The front is finished to remove the texture floating layer to ensure that the depth of the pore-like depression is consistent. The back is finished to improve the thickness of the substrate. Finally, the total thickness of the finished product is controlled at 0.65±0.01mm. After finishing, the back is subjected to a second ultra-fine grinding treatment using a 400-mesh sanding roller with a grinding pressure of 0.12MPa to form a fine, flattened fiber layer with a grinding length of 0.01mm.

[0037] (5) Post-processing: The refined semi-finished product is washed with warm water at 50°C for 3 minutes, then immersed in a solution containing 3g / L of organosilicon softener for 2 minutes, with a liquid yield of 70%, and dried at 110°C for 3 minutes. After cooling, it is rolled up to obtain a simulated leather lining microfiber synthetic leather.

[0038] In the finished product obtained in this embodiment, the thickness of the waterborne polyurethane adhesive transition layer is 0.02 mm.

[0039] Example 2: A specific two-cut manufacturing process for imitation leather lining microfiber synthetic leather, including the following steps:

[0040] (1) Substrate pretreatment: Take a 0.6 mm thick island-type microfiber nonwoven fabric (the marine phase is polyethylene, the island phase is polyester, and the composite ratio is 50:50), treat it with 10% sodium hydroxide solution at 98℃ for 50 min to perform alkali reduction fiber opening, remove the marine phase components, wash it with hot water until neutral, pre-shape it at 120℃ for 3 min, and then use a 280 mesh sander to lightly abrade the back of the substrate with an abrasion pressure of 0.25 MPa to obtain an island-type three-dimensional mesh microfiber nonwoven fabric substrate with a fiber filament fineness of 0.08D and a porosity of 71%, for later use;

[0041] (2) Pre-fabrication of textured surface layer: Matte release paper (60° gloss 2.7) with disordered imitation natural first-grain leather grain texture is selected. Microporous polyurethane slurry (polyurethane solid content 32%, DMF / toluene = 7:3, 0.8wt% organosilicon powder and 4.7wt% polyethylene glycol 400 as water-soluble pore-forming agent) is coated on the surface of the release paper with a 120-mesh squeegee. It is then dried at 80℃ for 3 min, 110℃ for 3 min and 130℃ for 3 min in sequence to form a polyurethane surface layer film with simulated leather texture, 0.05 mm thick, with internal pore diameter of 3-6 μm and interconnected micropores. The pore-like depressions on the outer surface texture have an equivalent diameter of 50 μm, a depression depth of 11 μm and a distribution density of 140 pores / cm. 2 The overall surface undulation difference is 12μm, ready for use;

[0042] (3) Rough finishing: Water-based polyurethane adhesive (28% solid content) is uniformly coated on the front side of the island-type three-dimensional mesh microfiber nonwoven fabric substrate using an 80-mesh roller coating method, with an adhesive application rate of 42g / m. 2 A polyurethane film with a simulated leather texture is bonded to a hot press roller at a temperature of 95℃, a pressure of 0.4MPa, and a bonding speed of 5m / min. After bonding, the film is left to stand and mature at 25℃ for 12 hours. After maturation, a belt-type slitting knife is used for the first trimming and thickness determination, with a cutting depth of 0.10mm / pass, cutting the overall thickness to 0.70±0.02mm to obtain a rough-trimmed semi-finished product.

[0043] (4) Second-cut finishing: The semi-finished product after rough finishing is cut a second time using a precision grinding wheel slicing machine with a feed rate of 0.03mm / pass. The front is finished to remove the texture floating layer to ensure that the depth of the pore-like depression is consistent. The back is finished to improve the thickness of the substrate. Finally, the total thickness of the finished product is controlled at 0.65±0.01mm. After finishing, the back is subjected to a second ultra-fine grinding treatment using a 500-mesh sanding roller with a grinding pressure of 0.15MPa to form a fine, flattened fiber layer with a grinding length of 0.015mm.

[0044] (5) Post-processing: The refined semi-finished product is washed with warm water at 50°C for 3 minutes, then immersed in a solution containing 4g / L of organosilicon softener for 2 minutes, with a liquid yield of 70%, and dried at 110°C for 3 minutes. After cooling, it is rolled up to obtain a simulated leather lining microfiber synthetic leather.

[0045] In the finished product obtained in this embodiment, the thickness of the waterborne polyurethane adhesive transition layer is 0.025 mm.

[0046] Example 3: A specific two-cut manufacturing process for simulated leather lining microfiber synthetic leather, including the following steps:

[0047] (1) Substrate pretreatment: Take a 0.6 mm thick island-type microfiber nonwoven fabric (the marine phase is polyethylene, the island phase is polyester, and the composite ratio is 55:45), treat it with 12% sodium hydroxide solution at 100℃ for 60 min to perform alkali reduction fiber opening, remove the marine phase components, wash it with hot water until neutral, pre-shape it at 120℃ for 3 min, and then use a 320 mesh sander to lightly abrade the back of the substrate with an abrasion pressure of 0.3 MPa to obtain an island-type three-dimensional mesh microfiber nonwoven fabric substrate with a fiber filament fineness of 0.12D and a porosity of 75%, for later use;

[0048] (2) Pre-fabrication of textured surface layer: Matte release paper (60° gloss 3.5) with disordered imitation natural first-grain leather grain texture engraved on the surface is selected. Microporous polyurethane slurry (polyurethane solid content 35%, DMF / toluene = 7:3, 1.2wt% organosilicon micro powder and 6.8wt% polyethylene glycol 400 as water-soluble pore-forming agent) is coated on the surface of the release paper with a 120-mesh squeegee. It is then dried at 80℃ for 4 min, 110℃ for 4 min and 130℃ for 4 min in sequence to form a polyurethane surface layer film with a thickness of 0.06 mm, an internal pore diameter of 5-8 μm and interconnected micropores with simulated leather texture. The equivalent diameter of the pore-like depressions on the outer surface texture is 65 μm, the depression depth is 16 μm and the distribution density is 170 / cm. 2 The overall surface undulation difference is 18μm, ready for use;

[0049] (3) Rough finishing: Water-based polyurethane adhesive (30% solid content) is uniformly coated on the front side of the island-type three-dimensional mesh microfiber nonwoven fabric substrate using an 80-mesh roller coating method, with an adhesive application rate of 48g / m. 2 A polyurethane film with a simulated leather texture is bonded to a hot press roller at a temperature of 100℃, a pressure of 0.5MPa, and a bonding speed of 4m / min. After bonding, the film is left to stand and mature at 25℃ for 12 hours. After maturation, a belt-type slitting knife is used for the first trimming and thickness determination, with a cutting depth of 0.12mm / pass, cutting the overall thickness to 0.70±0.02mm to obtain a rough-trimmed semi-finished product.

[0050] (4) Second-cut finishing: The semi-finished product after rough finishing is cut a second time using a precision grinding wheel slicing machine with a feed rate of 0.04mm / pass. The front is finished to remove the texture floating layer to ensure that the depth of the pore-like depression is consistent. The back is finished to improve the thickness of the substrate. Finally, the total thickness of the finished product is controlled at 0.65±0.01mm. After finishing, the back is subjected to a second ultra-fine grinding treatment using a 600-mesh sanding roller with a grinding pressure of 0.18MPa to form a fine, flattened fiber layer with a grinding length of 0.02mm.

[0051] (5) Post-processing: The refined semi-finished product is washed with warm water at 50°C for 3 minutes, then immersed in a solution containing 5g / L of organosilicon softener for 2 minutes, with a liquid yield of 70%, and dried at 110°C for 3 minutes. After cooling, it is rolled up to obtain a simulated leather lining microfiber synthetic leather.

[0052] In the finished product obtained in this embodiment, the thickness of the waterborne polyurethane adhesive transition layer is 0.03 mm.

[0053] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that the water-based polyurethane bonding transition layer is omitted. Instead, the polyurethane surface film with simulated leather texture is directly bonded to the front of the substrate with solvent-based polyurethane adhesive, without setting a separate water-based bonding transition layer. All other raw materials, proportions and process steps are the same as in Example 2.

[0054] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that the traditional production process of first splitting the substrate and then pasting the surface is adopted. That is, the 0.6mm island-type microfiber nonwoven fabric is first split into pieces and the thickness is determined after alkali reduction fiber opening. Then, an adhesive is coated on the substrate surface and a polyurethane surface film is pasted on. After pasting, no rough trimming or fine trimming is performed. It directly enters the post-processing process. The other raw materials and proportions are the same as those in Example 2.

[0055] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that the release paper used in step (2) is plain matte release paper, which does not have the texture of imitation natural first-grain leather. The outer surface of the resulting polyurethane surface film is flat and textureless. The other raw materials, proportions and process steps are the same as those in Example 2.

[0056] Performance testing:

[0057] The simulated leather lining microfiber synthetic leathers prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to the following performance tests, while a group of commercially available ordinary microfiber lining leathers was set up as a control group. Specific test items and standards are as follows:

[0058] 1. Air and moisture permeability test: Following GB / T 1037-2021 "Test Method for Water Vapor Permeability of Plastic Films and Sheets - Cup Method", the water vapor permeability of each sample was tested using a water vapor transmission rate tester. The test temperature was 38℃, the relative humidity was 90%, and the sample test area was 0.00283 m². 2 Each group of samples was tested 3 times and the arithmetic mean was taken.

[0059] 2. Abrasion resistance test: According to GB / T 21196.2-2007 "Textiles - Martindale method - Determination of abrasion resistance of fabrics - Part 2: Determination of sample breakage", the abrasion resistance tester was used to test each sample. The abrasive was standard wool felt, the load pressure was 595g, and the number of frictions when the sample surface showed pilling or coating damage was recorded.

[0060] 3. Flexural endurance test: According to the flexural endurance test method in GB / T 20991-2007 "Test Method for Footwear of Personal Protective Equipment", the flexural endurance tester was used to conduct continuous bending tests on each sample. The bending angle was 22.5° and the bending frequency was 100 times / min. The number of bends when visible cracks appeared on the sample surface was recorded.

[0061] 4. Thickness uniformity test: In accordance with GB / T 6672-2001 "Mechanical measurement method for determination of thickness of plastic film and sheet", a thickness gauge is used to measure the thickness at 10 points at equal intervals along the width direction of each sample, and half of the difference between the maximum and minimum thickness values ​​is calculated as the thickness tolerance.

[0062] 5. Peel strength test: According to the peel strength test method in GB / T 8949-2008 "Polyurethane Dry Process Artificial Leather" standard, the surface layer and the base material are peeled together in a 180° direction using a universal testing machine at a tensile speed of 100 mm / min, and the average force value during the peeling process is recorded.

[0063] 6. Surface gloss test: According to the gloss test method in GB / T 8949-2008, the gloss of the front of each sample was tested using a 60° angle gloss meter. The arithmetic mean of 5 points in each group was taken.

[0064] 7. Color fastness to rubbing test: In accordance with GB / T 29865-2013 "Textiles - Tests for color fastness to rubbing - Small area method", the color fastness to rubbing of each sample was tested using a color fastness to rubbing instrument, and the gray scale was used for rating; the experimental results are shown in Table 1.

[0065] Table 1 Performance Test Results

[0066]

[0067] Data Analysis:

[0068] As can be seen from the test results in Table 1, the simulated leather lining microfiber synthetic leather prepared in Examples 1 to 3 of the present invention is superior to the comparative example and the commercially available control group in all performance indicators, with Example 2 showing the best overall performance.

[0069] In terms of air permeability and moisture permeability, the water vapor transmission rate of Example 2 reached 473 g / (m³). 2 •24h), compared to 362g / (m²) in Comparative Example 1 2 • 24h) increased by approximately 30.7%, compared to 279g / (m 2 The water vapor permeability was increased by approximately 69.5% (24h). This difference mainly stems from two aspects: First, the surface film of this invention has interconnected micropores of 2-8μm inside, providing a moisture permeation channel for water vapor, while ordinary dense PU surface layers block the moisture permeation path; Second, the water-based polyurethane bonding transition layer avoids the swelling and filling of the microfiber substrate's pore structure by solvent-based adhesives, preserving the three-dimensional interconnected pores of the substrate. In Comparative Example 1, because solvent-based adhesives were used for direct bonding, the adhesives penetrated into the surface pores of the substrate, causing some pores to be blocked, thus significantly reducing the water vapor permeability. The water vapor permeability of Examples 1 and 3 were 398 and 429 g / (m³), respectively. 2 The moisture permeability (24h) is at a high level, indicating that within the range of surface micropore size and organosilicon powder content defined by this invention, the moisture permeability can be effectively guaranteed.

[0070] In terms of abrasion and flexural resistance, the Martindale of Example 2 achieved 36,130 abrasion cycles and 79,230 flexural crack occurrences, representing improvements of approximately 82% and 75% respectively compared to Comparative Example 1, and approximately 152% and 154% compared to the commercially available control group. The improved abrasion and flexural resistance is mainly attributed to the introduction of a water-based adhesive transition layer: this layer enhances the interfacial bonding strength between the topcoat and the substrate. Example 2 achieved a peel strength of 15.7 N / cm, an improvement of approximately 99% compared to 7.9 N / cm in Comparative Example 1. The topcoat is less prone to separation from the substrate under repeated bending and friction, thus delaying coating peeling and surface fuzzing. Comparative Example 1, lacking a transition layer for buffering, exhibited a significant hardness difference between the topcoat and the substrate, resulting in interfacial stress concentration and a tendency for interfacial separation and surface cracks after repeated bending. Comparative Examples 2 and 3 have the same material structure as Example 2 (only the process sequence or surface texture is different), and their wear resistance and flexural strength are similar to those of Example 2, further illustrating that the wear resistance and flexural strength are mainly determined by the four-layer composite structure.

[0071] Regarding thickness uniformity, the thickness tolerance of Example 2 was only ±0.007mm, far superior to ±0.026mm of Comparative Example 2 and ±0.033mm of the commercially available control group. This result fully verifies the effectiveness of the two-cut lamination process: the first rough cut, after lamination, uses a belt-type slitting blade to cut the semi-finished product to approximately 0.70mm, eliminating thickness deviations caused by lamination adhesive layer thickness fluctuations and interface bubble protrusions in one go; the second fine cut uses a precision grinding wheel slitting machine with a smaller feed rate to precisely correct the front and back sides, controlling the finished product thickness near the target value. The division of labor and cooperation between the two cutting processes reduces the thickness tolerance by approximately 73.1% compared to the traditional process of first cutting the sole material and then laminating, which is of practical significance for the cutting utilization rate and sewing consistency of shoe lining materials. Comparative Example 2 uses a traditional process, where the thickness deviation after lamination cannot be eliminated by subsequent processes, resulting in a significantly larger thickness tolerance.

[0072] Regarding the simulated leather texture, Example 2 exhibits a 60° gloss level of 2.7, presenting a matte effect, similar to the gloss characteristics of natural top-grain leather; its dry rubbing color fastness reaches level 4-5, meeting the requirements for lining materials. Comparative Example 3, due to its plain, textureless surface film, while possessing similar breathability, abrasion resistance, and thickness uniformity to Example 2, has a 60° gloss level as high as 7.2, resulting in a smooth, reflective surface lacking the natural texture and matte feel of genuine leather, making it visually identifiable as a synthetic material. This comparison, from the opposite perspective, verifies the necessity of the disordered grain-like texture design of this invention for enhancing the simulated leather texture. The gloss levels of Examples 1 and 3 are 3.4 and 3.7, respectively, both within the matte range, indicating that within the texture parameters defined in the claims, the matte effect of simulated leather can be stably achieved.

[0073] In summary, this invention, through the synergistic combination of a composite structure and a two-step bonding process, achieves improvements in simulated leather feel, breathability and moisture permeability, abrasion and fold resistance, and thickness uniformity. Furthermore, stable technical effects are achieved within the numerical range defined by this invention. The finished product exhibits superior overall performance compared to existing microfiber lining leather and ordinary PU synthetic leather, making it suitable as a lining material for footwear and bags.

[0074] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A simulated leather lining made of microfiber synthetic leather, characterized in that, From front to back, the layers consist of a simulated leather texture microporous polyurethane surface layer, a water-based polyurethane bonding transition layer, an island-type three-dimensional mesh microfiber nonwoven fabric substrate, and an ultra-fine brushed back layer. The simulated leather texture microporous polyurethane surface layer is a polyurethane film with simulated leather texture. Its outer surface has a disordered imitation natural top-grain leather grain texture. The texture consists of irregularly distributed pore-like depressions and smooth grain-like protrusions. The equivalent diameter of the pore-like depressions is 35-65 μm, the depression depth is 7-16 μm, and the distribution density per unit area is 110-170 per cm². 2 The overall surface undulation difference does not exceed 18μm, and there are no periodic repeating units; The original thickness of the island-type three-dimensional mesh microfiber nonwoven fabric substrate is 0.6 mm. After fiber opening and weight reduction treatment, it forms a three-dimensional through-pore structure with a fiber filament fineness of 0.05 to 0.12 D and a porosity of 68% to 75%.

2. The simulated leather lining microfiber synthetic leather according to claim 1, characterized in that, The simulated leather texture microporous polyurethane surface layer has a thickness of 0.04 to 0.06 mm, and is uniformly distributed with interconnected micropores with a pore size of 2 to 8 μm. The surface layer contains 0.5 to 1.2 wt% organosilicon micro powder.

3. The simulated leather lining microfiber synthetic leather according to claim 1, characterized in that, The thickness of the waterborne polyurethane adhesive transition layer is 0.02 to 0.03 mm, and it is formed by curing with waterborne polyurethane adhesive.

4. The simulated leather lining microfiber synthetic leather according to claim 1, characterized in that, The abrasion length of the ultrafine abrasion back layer is 0.01 to 0.02 mm, and the surface fibers are fine and flat.

5. A two-stage manufacturing process for preparing the simulated leather lining microfiber synthetic leather according to any one of claims 1 to 4, characterized in that, Includes the following steps: (1) Substrate pretreatment: Take a 0.6mm thick island-type microfiber nonwoven fabric, and after alkali reduction fiber opening, water washing, and 120℃ pre-forming, perform light abrasion treatment on the back side to obtain island-type three-dimensional mesh microfiber nonwoven fabric substrate for use. (2) Textured surface layer prefabrication: Select matte release paper with disordered imitation natural first-grain leather grain texture, coat the surface of the release paper with microporous polyurethane slurry containing 0.5 to 1.2 wt% organosilicon micro powder, and dry in sections to form a polyurethane surface layer film with simulated leather texture for later use. (3) Rough trimming: Water-based polyurethane adhesive is uniformly coated on the front side of the island-type three-dimensional mesh microfiber nonwoven fabric substrate. The polyurethane surface film with simulated leather texture is bonded by hot press roller. After curing, the first trimming and thickness determination are carried out to cut the overall thickness to 0.70±0.02mm to obtain the semi-finished product after rough trimming. (4) Second-cut finishing: The semi-finished product after rough finishing is precision-cut a second time. The texture layer on the front is finely finished to ensure that the texture depression depth is consistent. The thickness of the base material on the back is finely finished. Finally, the total thickness of the finished product is controlled at 0.65±0.01mm. After finishing, the back is subjected to a second ultra-fine grinding process. (5) Post-processing: After washing, softening, drying at 110℃ and rolling, a simulated leather lining microfiber synthetic leather is obtained.

6. The two-cut manufacturing process for the lining of simulated leather microfiber synthetic leather according to claim 5, characterized in that, In step (1), the alkali reduction fiber opening process uses a sodium hydroxide solution with a mass fraction of 8% to 12%, the treatment temperature is 95 to 100°C, and the treatment time is 40 to 60 minutes.

7. The two-cut manufacturing process for the simulated leather lining microfiber synthetic leather according to claim 5, characterized in that, The temperatures for the segmented drying in (2) are 80℃, 110℃ and 130℃ respectively, and the drying time for each segment is 2 to 4 minutes.

8. The two-cut manufacturing process for the lining of simulated leather microfiber synthetic leather according to claim 5, characterized in that, The temperature of hot pressing in (3) is 90-100℃, the pressure is 0.3-0.5MPa, and the bonding is left to stand for 12 hours after bonding.

9. The two-cut manufacturing process for the lining of simulated leather microfiber synthetic leather according to claim 5, characterized in that, In step (3), the first sectioning is performed using a strip cutting tool with a feed rate of 0.08 to 0.12 mm per pass.

10. The two-cut manufacturing process for the lining of simulated leather microfiber synthetic leather according to claim 5, characterized in that, In step (4), the second finishing process uses a precision grinding wheel slicing machine with a feed rate of 0.02 to 0.04 mm / pass.